2022
DOI: 10.1099/jmm.0.001537
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli can cause cystitis at extremely low inocula in a pig model

Abstract: Urinary tract infection (UTI) is one of the most common bacterial infections worldwide. Experimental models that accurately reflect the high susceptibility to UTI in humans have, however, been lacking. This situation has limited detailed research into the early bladder colonization by uropathogens and the early innate defence mechanisms elicited to prevent this. We recently presented a model of urinary tract infection in pigs, animals that are naturally susceptible to UTI and have greater similarity to the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…23 As a result of the high incidence of UPEC-associated UTIs, UPEC is the predominant model species used in experimental UTI studies and, to our knowledge, the only uropathogen species used in porcine UTI studies. 9,10,21,24 Therefore, in studies of UPEC or other members of the Enterobacteriaceae family, using selective blue agar is an excellent approach to minimize contamination when clean-catching urine specimens. When urine specimens from clean-catch were plated on a universal medium, 5% blood agar, bacterial contaminants were frequently detected (98% of samples) and occasionally appeared in relatively high numbers (13% of samples at 10 3 CFU · ml –1 ), suggesting that universal growth media can be a challenge if working with Gram-positive uropathogenic model organisms, such as Enterococcus faecalis or Staphylococcus saprophyticus , that is, bacterial species that are not culturable on selective blue agar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23 As a result of the high incidence of UPEC-associated UTIs, UPEC is the predominant model species used in experimental UTI studies and, to our knowledge, the only uropathogen species used in porcine UTI studies. 9,10,21,24 Therefore, in studies of UPEC or other members of the Enterobacteriaceae family, using selective blue agar is an excellent approach to minimize contamination when clean-catching urine specimens. When urine specimens from clean-catch were plated on a universal medium, 5% blood agar, bacterial contaminants were frequently detected (98% of samples) and occasionally appeared in relatively high numbers (13% of samples at 10 3 CFU · ml –1 ), suggesting that universal growth media can be a challenge if working with Gram-positive uropathogenic model organisms, such as Enterococcus faecalis or Staphylococcus saprophyticus , that is, bacterial species that are not culturable on selective blue agar.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the potential influence of the experimental inoculation on the course on infection is difficult to assess; however, in a previous study we showed that inoculation with a non-pathogenic Pseudomonas aeruginosa using the same protocol did not result in any detectable bacteria 24 h after inoculation, suggesting that the experimental infection procedure does not lead to bladder colonization. 9 Since the main objective of this study was to develop a protocol for clean-catching urine specimens and to evaluate the quality in terms of contamination, we find it justified to use control specimens from the same animals before they are subjected to experimental inoculation. This also reduces the number of animals needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The authors have carried out extensive work with a porcine model of experimental urinary tract infection (UTI), in which catheterisation has been a fundamental procedure. 2,3,[17][18][19] It has also been the methodological step associated with most uncertainty, as catheterisation in some animals occasionally would take considerable time (up to an hour), similar to reports from others. 14 Consequently, controlled inoculation or timely urine sampling would occasionally be delayed because the catheter was difficult to insert, thus contributing to potential bias.…”
Section: Introductionmentioning
confidence: 67%